Surgical resection for advanced thymic malignancy with pulmonary hilar invasion using hemi-clamshell approach - Fujiwara, Ayako (J Thorac Dis, 2018)
BACKGROUND: The hemi-clamshell (HCS) approach provides a wide anterior view of the mediastinum as well as outstanding exposure of the pulmonary hilum. Here, we evaluated the utility and outcomes of this approach in cases of advanced thymic malignancy with hilar invasion. METHODS: We performed a retrospective analysis of 14 patients with thymic epithelial malignancy surgically resected with an HCS approach. All required lung resection because of suspected pulmonary hilar vessel invasion. RESULTS: Histological findings showed that 8 patients had a thymoma and 6 a thymic carcinoma. Thirteen patients underwent lung resection, a lobectomy or bilobectomy in 8 and wedge resection in 5, while 1 had an exploratory thoracotomy. Seven patients with a thymoma underwent resection of disseminated lesions and 8 of 10 who underwent phrenic nerve resection received diaphragmatic plication through an HCS procedure. There were no postoperative mortalities. Macroscopic complete surgical resection was achieved in 13 cases. CONCLUSIONS: An HCS approach was helpful for lung resection performed for advanced thymic malignancy with hilar invasion by providing multiple access paths to the tumor and hilum, allowing for a sufficient surgical margin. Furthermore, it was useful for resection of disseminated lesions and diaphragmatic plication.